Analysis of river water pollution control due to activities gold mining: Causes, impacts, and effective and sustainable control efforts - Utami, Melliza Pretty Putri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study examines river water pollution due to gold mining activities in Indonesia and its control efforts. This pollution is caused by the use of hazardous chemicals such as mercury and cyanide in the gold extraction process, as well as the disposal of mining waste without adequate treatment. The impacts of pollution include damage to aquatic ecosystems, decreased water quality, and threats to human health. Methods: The research methodology uses a qualitative approach with secondary data analysis from various sources such as journal articles, government reports, and case studies. Data are analyzed using triangulation techniques to ensure the validity and reliability of the information. Findings: The discussion shows that water pollution due to gold mining, especially illegal activities, has caused significant declines in water quality in various regions in Indonesia. The impacts of pollution include threats to human health, damage to aquatic ecosystems, decreased water quality, and disruption to the livelihoods of communities that depend on water resources. Conclusions: Emphasize the importance of pollution control through the application of environmentally friendly technologies, strict regulations, and public education. Recommendations for further research include further study of the long-term impacts of mercury pollution, development of more efficient waste treatment technologies, and exploration of alternative livelihoods for communities around mining areas. Novelty/Originality of This Study: This study lies in its comprehensive analysis of river water pollution from gold mining in Indonesia, integrating environmental, health, and socio-economic perspectives to propose sustainable pollution control strategies and alternative livelihood solutions.